Share on vk Share on google_plusone_share Share on twitter Share on email More Sharing Services Changes in the structure of the fungal soil community induced by contamination with high oil contents under the laboratory conditions - L.R. Biktasheva; S.Y. Selivanovskaya; P.Y. Galitskaya (Учёные записки Казанского университета: Серия Естественные науки)
Changes in the fungal communities of three oil-contaminated soil samples (D, S, and C) with different contents of organic carbon (0.8%, 1.9%, and 4.5%) were investigated. All samples were contaminated with oil at a concentration of 120 g kg–1 and incubated for 120 days. The addition of oil to the soil induced an approximately two-fold decrease in the abundance of fungi with its subsequent restoration up to the baseline level in samples S and C. In sample D, however, it remained low throughout the experiment. With the help of the Illumina MiSeq high-throughput sequencing, it was revealed that the fungal communities of the oil-contaminated samples S and C were least resistant to the oil contamination (the first changes were registered on the third day of incubation) as compared to sample D that suffered the first structural changes on the 30th day of the experiment. After 120 days of the incubation, selective dominance of the following fungi was recorded: sample D – the genus Fusarium (34%) and the family Clavicipitaceae (20%); sample S – the genus Fusarium (82%); sample C – the genera Fusarium (56%) and Mortierella (21%). The results of the NMDS analysis demonstrate that the communities of all oil-contaminated samples were reliably different from the communities of control soils since the 30th day of the experiment. Notably, the differences observed intensified with time.